Chemical inhibition of reversible decomposition for efficient and super-stable perovskite solar cells. (February 2020) - Chen, Cong; Zhuang, Xinmeng; Bi, Wenbo; Wu, Yanjie; Gao, Yanbo; Pan, Gencai; Liu, Dali; Dai, Qilin; Song, Hongwei
Abstract: Despite the remarkable photovoltaic characteristics and printability of perovskite solar cells, their intrinsic instability has been the most serious drawback toward future commercialization. In this work, we have investigated the stability of perovskite films in terms of morphology, electronic properties and chemical compositions. Specifically, the chemical decomposition inhibition strategy was introduced in perovskite films through iodine bromide to modify the crystal defects, leading to PSCs with suppressed hysteresis effects, superior durability and attractive PCE of 21.5%. Femto-second transient absorption spectra and GIWAXS measurements provide deep insight into the reduced carrier recombination and indicate the improved crystallinity of the modified perovskite films. Furthermore, an efficient hole-transporting material, PDPP4T, without using any doping process is applied to achieve PSCs with enhanced open-circuit voltage and better repeatability. As a consequence, the modified PSCs could maintain 82% of their initial efficiency after 5000 h of storage in ambient conditions and 90% of their initial efficiency after 1000 h of light soaking process. An excellent water resistance up to 100 h of the PSCs is also obtained by encapsulation technology. Besides, after coating Ce 3+ -CsPbI3 nanocrystals as luminescent down-shifting layers on the front side of the PSCs, the PCE of the device was further improved to 22.16%. Graphical abstract: The chemical decomposition inhibition strategy was introduced in perovskite films through iodine bromide to modify the crystal defects, leading to PSCs with suppressed hysteresis effects, attractive PCE of 21.5% and superior durability of 5000 h. Image 1 Highlights: The chemical decomposition inhibition strategy by IBr could induce superior durability of 5000 h. The IBr modified PSCs could achieve a remarkable PCE of 21.5%. Novel hole-transporting material PDPP4T without doping help to enhance the Voc and better repeatability of devices. The encapsulated PSC exhibits an excellent resistance effect up to 100 h in water. Femto-second TAS spectra and GIWAXS measurements prove the reduced carrier recombination processes.